Betel chewing and arecoline affects eotaxin-1, asthma and lung function. - Tsu-Nai Wang (Public Library of Science (PLoS), 2014)
Background Betel nut is commonly used in many countries. Despite evidence suggesting an association with asthma, few studies have investigated the connection between betel nut use and asthma; thus, the underlying mechanism for the association with asthma is also unclear. The aim of this study was to investigate the association between betel chewing and asthma as well as the associations of plasma arecoline (a biomarker for exposure) and eotaxin-1 (a potential mediator) with asthma and lung function. Methods We recruited 600 hospital-based asthmatic patients and 1200 age- and gender-matched community controls in southern Taiwan. To clarify the mechanism of action for eotaxin-1 in the association between betel chewing and asthma, we also designed an in vitro experiment to study the functional associations between arecoline exposure and eotaxin-1 levels. Results A significant association was found between asthma and current betel chewing (adjusted odds ratio 2.05, 95% CI = 1.12-3.76), which was independent of potential confounders but was attenuated following adjustment for eotaxin-1. Arecoline and eotaxin-1 levels were positively correlated (Spearman r = 0.303, p = 0.02), while arecoline and arecaidine were negatively correlated with lung function. Functionally, arecoline alone does not induce eotaxin-1 release in vitro from dermal and gingival fibroblasts. However, in the presence of IL-4 and TNF-alpha, arecoline at 100 μg/ml induced more eotaxin-1 release than arecoline at 0 μg/ml (2700±98 pg/ml vs 1850±142 pg/ml, p = 0.01 in dermal fibroblast cells, and 1489±78 pg/ml vs 1044±95 pg/ml, p = 0.03 in gingival fibroblast cells, respectively). Conclusion Betel chewing is associated with asthma in this population, with arecoline induction of eotaxin-1 supported as a plausible causal pathway.